1998
DOI: 10.1148/radiology.208.2.9680581
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic hyperplasia: US-guided transrectal urethral enlargement with radio frequency--initial results in a canine model.

Abstract: Transrectal RF urethral enlargement is feasible and safe in animals and merits investigation for alleviating urethral obstruction due to benign prostatic hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In this study, we report on an experiment involving ILC in an in vivo canine prostate model. Canine prostate has topographical features comparable to the human prostate, and this study represents a logical preliminary stage before designing human prostate protocols (18, 19). One of the anticipated outcomes of this study was to determine whether quantitative MR‐thermal mapping can predict of thermal damage in the prostate, thereby providing useful operating parameters with which to conduct future human prostate studies.…”
mentioning
confidence: 99%
“…In this study, we report on an experiment involving ILC in an in vivo canine prostate model. Canine prostate has topographical features comparable to the human prostate, and this study represents a logical preliminary stage before designing human prostate protocols (18, 19). One of the anticipated outcomes of this study was to determine whether quantitative MR‐thermal mapping can predict of thermal damage in the prostate, thereby providing useful operating parameters with which to conduct future human prostate studies.…”
mentioning
confidence: 99%
“…Another preclinical study that showed promising results, but was never, to our knowledge, transferred into a published clinical study, was the work by Ahmed et al investigating the combination of RF ablation and lipo‐DOX . A few reports on the use of RF ablation as the sole treatment for dogs with non‐cancerous disease exist . However, the improved efficacy in the Ahmed study when combining RF with lipo‐DOX compared with either of the modalities, indicates that these methods should be employed together for cancer treatment.…”
Section: Primary Lessons From Canine and Feline Liposomal Chemotherapmentioning
confidence: 99%
“…Minimally invasive therapies have gained increasing attention in the last decade as an alternative to standard surgical therapy (Hill and ter Haar 1995, Murphy and Gill 2001, Chin and Pautler 2002, Goldberg and Ahmed 2002, Ogan and Cadeddu 2002, Tunuguntla and Evans 2002. They are being investigated for the treatment of many diseases such as primary hepatocellular carcinoma (HCC) (Goldberg 2001, Haemmerich et al 2001, Goldberg and Ahmed 2002, lower urinary tract symptoms due to benign prostatic hyperplasia (Goldberg et al 1998, Beerlage et al 2000, Tunuguntla and Evans 2002 and small renal-cell carcinoma (RCC) (Gervais et al 2000, Murphy and Gill 2001, Chin and Pautler 2002, Ogan and Cadeddu 2002. Temperatures greater than 42 • C are considered potentially lethal, depending on the duration of application (Rosner et al 1996), and temperatures greater than 60 • C are associated with uniform tissue necrosis.…”
Section: Introductionmentioning
confidence: 99%